Analisis Pemahaman Siswa Kelas V terhadap Materi Campuran dan Larutan dalam Kehidupan Sehari-hari di SD Negeri 101765 Bandar Setia - Frischa Amalia Putri; Aulia Ramadhani; Suyit Ratno; Chelsea Nabilla Azzahra; Desni Febriyola; Fauzia Syahira Maghfirah; Monica Celia Barros; Mutiara Cahayani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study aims to analyze the understanding of fifth-grade students of SD Negeri 101765 Bandar Setia regarding the material of mixtures and solutions in everyday life and identify factors that influence this understanding. This study used a mixed methods approach with a descriptive design. The research subjects consisted of 21 fifth-grade students and 1 homeroom teacher. Data were collected through questionnaires, essay tests, and interviews, then analyzed descriptively and data triangulation was conducted. The results of the study indicate that most students have a good understanding of the material of mixtures and solutions, especially on concepts related to examples in everyday life. However, there are still some students who have difficulty in distinguishing homogeneous and heterogeneous mixtures. Student understanding is influenced by the use of concrete media, direct learning experiences, and teacher learning strategies. Thus, learning based on direct experience through the use of concrete media and simple experiments is effective in improving students' understanding of the material of mixtures and solutions.